Perceptions of HIV cure and willingness to participate in HIV cure-related trials among people enrolled in the Netherlands cohort study on acute HIV infection - Pien van Paassen; Maartje Dijkstra; Holly L. Peay; Casper Rokx; Annelies Verbon; Peter Reiss; Jan M. Prins; Gail E. Henderson; Stuart Rennie; Pythia T. Nieuwkerk; Godelieve J. de Bree (Elsevier, 2022)
Background: People who initiate antiretroviral therapy (ART) during acute HIV infection are potential candidates for HIV cure-related clinical trials, as early ART reduces the size of the HIV reservoir. These trials, which may include ART interruption (ATI), might involve potential risks. We explored knowledge and perception of HIV cure and willingness to participate in cure-related trials among participants of the Netherlands Cohort Study on Acute HIV infection (NOVA study), who started antiretroviral therapy immediately after diagnosis of acute HIV infection. Methods: We conducted 20 in-depth qualitative interviews with NOVA study participants between October-December 2018. Data were analyzed thematically, using inductive and iterative coding techniques. Findings: Most participants had limited knowledge of HIV cure and understood HIV cure as complete eradication of HIV from their bodies. HIV cure was considered important to most participants, mostly due to the stigma surrounding HIV. More than half would consider undergoing brief ATI during trial participation, but only one person considered extended ATI. Viral rebound and increased infectiousness during ATI were perceived as large concerns. Participants remained hopeful of being cured during trial participation, even though they were informed that no personal medical benefit was to be expected. Interpretation: Our results highlight the need for thorough informed consent procedures with assessment of comprehension and exploration of personal motives prior to enrollment in cure-related trials. Researchers might need to moderate their expectations about how many participants will enroll in a trial with extended ATI.